Improving The Effectiveness of School Management: Training of School Principals In The Preparation of Lesson Plans, Improvement of Facilities and Infrastructure, and Handling Delays In Submitting Student Assignments - Dikalni, Dikalni; Louise, Yorenda; Manuramadanti, Noprima; Sari, Uci Purnama (PT. Marosk Zada Cemerlang, 2024)
Improving the effectiveness of school management is essential to achieving educational goals. The problem of this research is how school principals receive training to prepare and develop effective Learning Implementation Plans. Some teachers do not have complete and detailed learning tools for the subjects taught, which causes the learning process to not run effectively and efficiently. Management of facilities and infrastructure is very important because educational institutions will be maintained, clearly useful, and can help the learning process. School officials must be responsible for facilities and infrastructure, especially the principal, and handle delays in school assignments, such as making homework assignments late or not. This research uses a qualitative approach. Qualitative research is one type of research that can be well described and commonly used. To prevent delays in submitting assignments, students must ask again for material they have not studied. This research examines the role of school principal training in preparing Learning Implementation Plans, improving facilities and infrastructure, and dealing with delays in submitting student assignments. This research found that this training helped school principals prepare better lesson plans, improve the quality of facilities and infrastructure, and the findings of this research have significant consequences for school management policy and practice. To improve school management performance, continuous and high-quality principal training is needed. In addition, educational institutions must improve facilities and infrastructure, as well as implement methods to reduce delays in submitting assignments.